Disruptive transformation in the transport industry: Autonomous vehicles and transportation-as-a-service - Torres, Peter S; George, Babu (International Journal of Emerging Trends in Social Sciences, 2023)
This paper seeks to explore the varying degrees of impact that Autonomous Vehicles and Transportation-as-a-Service will have on several key industries, and how players in those industries might adapt their business strategies to prepare for this revolution. Systematic literature review. Transportation-as-a-Service is still in its infancy when it comes to commercial trucking. The concurrent developments in the autonomous vehicle technologies opens up additional opportunities for disruptive transformations. The scholarly literature is lagging behind trade reports and the current review is an attempt to claim this space. New players might take birth to cater to the emerging needs and opportunities. There are losers and gainers among the existing players. Also, overall, these changes will contribute to greater sustainability in transportation. Implications for Auto Manufacturers, Auto Dealerships, Oil and Energy Companies, Battery Manufacturers, Tech Companies, Insurance Firms, and National Governments are discussed. One specific implication is an overriding message for adaptability to fully leverage the benefits of these disruptive innovations.